'A Shape … Crouching within the Shadow of a Tomb': Shelley's Qualified Apocalypse in 'The Triumph of Life'. Issue 1 (31st March 2016) - Williams, Merle
Abstract : Apocalyptic imaginings are not uncommon in British Romantic poetry, especially in the work of Blake and Shelley. While 'The mask of Anarchy' is probably Shelley's most overtly apocalyptic piece, 'The triumph of life' may be read as tracing a 'qualified apocalypse' by drawing on insights provided by Paul de Man's influential deconstructive account in 'Shelley disfigured'. Following this trajectory, 'The triumph' is shown to treat sustained Enlightenment confidence in the capacities of reason as disfiguring and defacing not only individual growth, but also the possibilities for constructive intellectual, social and political activity in the European tradition. Shelley's strongly ethical criticism of such modes of engagement is linked through Queen Mab to the Levinasian notion of 'the face' and the closely related ethical enquiry of Jacques Derrida. Universalising rationalist principles that degrade 'the face' by stunting imaginative potential or relying on expedient political compromises are consistently criticised. Yet careful examination of the complex apocalyptic erasures and disfigurings of 'The triumph of life' suggests that they release a series of textual (and subtextual) reconfigurations – even transfigurations – which serve to restore the promise of both philosophical and spiritual creativity. Through this movement, vital aspects of European cultural achievement are subtly renewed or redeemed.